The clinical and genetic aspects of six individuals with GH1 variants and isolated growth hormone deficiency type II - Huang, Xiaozhen; Chen, Hong; Shangguan, Huakun; Wu, Wenyong; Ai, Zhuanzhuan; Chen, Zhifeng; Chen, Ruimin (Frontiers in Endocrinology, 2024)
Background: Isolated growth hormone deficiency type II (IGHD II) is an autosomal dominant disorder characterized by a GH1 gene variant resulting in a significant reduction in growth hormone (GH) secretion and a subsequent decrease of plasma insulin-like growth factor 1 (IGF-1) levels and eventual growth impairment.Objective: This study aimed to identify causative variants in six Chinese families with IGHD II, exploring both clinical and genetic characteristics.Methods: Detailed clinical data, including clinical presentations, physical charateristics, medical and family histories, as well as genetic test results, were systematically examined.Results: Six children, comprising four males and two females, with a mean age of 4.64±1.15 years, exhibited short stature with a mean height of -3.95±1.41 SDS.Four of them had a family history of short stature, while one patient presented with pulmonary hypertension. All children demonstrated GH deficiency in growth hormone stimulation tests (mean peak GH value: 2.83 ± 2.46 ng/mL). Exome sequencing for the six patients and targeted gene sequencing for their family members revealed heterozygous variants in the GH1 gene, including Exon2-5del, c.334T>C, c.291+1G>A, c.291+2T>A, 1.5 kb deletion, and 1.7 kb deletion, with four variants being novel. Four patients underwent human recombinant growth hormone (rhGH) replacement therapy, initiating treatment at a mean age of 4.6±0.7 years. The mean height increase in patients was 1.21 ± 0.3 SDS in the first six months of treatment and 1.79 ± 0.15 SDS in the first year.Our findings contribute to expanding the genotypic and phenotypic spectra of individuals with IGHD II.